Beyond Boundaries: Examining Land Disputes and Their Resolution in Baguio City - Elvis G. Bugtong; Johnson W. Mangsi; Crisselda S. Felix; Rona Angelie G. Allaga; Dalyne B. Bagsang; Almira L. Delico; Tessie B. Lingbanan; Drazen A. Palaez (Future Science / FSH-PH Publications, 2026)
This research study was about land conflicts in Baguio City. Forty-two professionals involved in land surveying and land conflicts resolution served as respondents. The descriptive research design was used with the questionnaire as the main data gathering instrument. Based on the data gathered, the study has found that boundary disputes, conflicting land claims, inheritance issues and land grabbing were among the most frequent and topmost cause of land conflicts in Baguio City; land conflicts have great effects on people and community; and the actions undertaken were very effective to resolve land conflicts. The conclusions are the following: land is a valuable and important resource to people, communities and the State which make conflicts inevitable to occur; illegal or fraudulent acquisition of land can cause hardships and great loss to people, communities and government; and conflicts can be resolved through judicial proceedings, mediation-arbitration, and other diplomatic means which are deemed very effective to concerned community, local and government leaders.